2013
DOI: 10.1007/s00784-013-1123-z
|View full text |Cite|
|
Sign up to set email alerts
|

Three-year clinical evaluation of a two-step self-etch adhesive with or without selective enamel etching in non-carious cervical sclerotic lesions

Abstract: Selective acid-etching of the enamel margins enhanced the performance of the two-step self-etch adhesive in terms of marginal discoloration and marginal adaptation at the enamel side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Based on our results, different etching techniques did not influence microleakage of Class V restorations prepared by Er:YAG laser and bur. Similar to our findings, Can Say, Ozel, Yurdagüven, and Soyman () stated that additional etching of the enamel cavosurface margins has no influence on adhesion.…”
Section: Discussionsupporting
confidence: 92%
“…Based on our results, different etching techniques did not influence microleakage of Class V restorations prepared by Er:YAG laser and bur. Similar to our findings, Can Say, Ozel, Yurdagüven, and Soyman () stated that additional etching of the enamel cavosurface margins has no influence on adhesion.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, there is an ongoing argument with respect to the efficacy of the sealing ability on the enamel surface with self-etch adhesives. Some authors supported the selective enamel etching by means of the supplementary use of phosphoric acid before the application of self-etch adhesive application ( 25 ) while certain other researchers claimed that the sealing ability of self-etch adhesives are similar to that of etch-and-rinse adhesives on the enamel margins ( 26 , 27 ). In agreement with the latter studies, the sealing performance of CSE and AEO was comparable with that of the etch-and-rinse adhesive, ASB2, used on enamel margins.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies have reported that selective enamel etching provided significantly better enamel bond strengths for sixth‐, seventh‐, and eighth‐generation bonding systems 9 , as well as universal adhesives, 10 than when the adhesives were used as self‐etch alone. Similarly, two in vivo studies 11,12 also indicated significantly improved performance of the selective enamel etch technique utilizing a one‐step universal adhesive 12 and a two‐step bonding system comprised of a self‐etch primer and separate bonding resin 11 . However, other studies 13‐17 failed to demonstrate a significant difference in clinical outcomes between the two techniques.…”
Section: Introductionmentioning
confidence: 99%